Effects of Ultraviolet (UV) treatment on the properties of black tilapia fish skins gelatin - ISMAIL, N.; IDRIS, M.I.; ABDULLAH, H.Z. (2020)
The aim of the study is to investigate the effects of ultraviolet (UV) treatment on the properties of black tilapia fish skins gelatin. The fish gelatin were investigated in terms of gel strength, functional group and the water contact angle of the gelatin. The UV treatment were irradiated with UVA and UVC at different time (0.5, 1.0, 1.5 and 2.0) h. The gel strength of gelatin gel significantly increases after UV irradiation for both UVA and UVC sample. The water contact angle of the gelatin was categorized as hydrophobic for both gelatin that treated with UVA and UVC which the angle were greater than 65°. The interactions and characteristic of functional groups for gelatin that treated with UV were analyzed via Fourier Transform Infrared Spectroscopy (FTIR). Results indicated that employing UV irradiation as an alternative method to enhance some of the quality attributes of fish gelatin. UVA is found to increase the properties of fish gelatin better than UVC at 1.5 h irradiation time.